The effects of personality and metacognitive beliefs on cognitive training adherence and performance. (November 2016) - Double, Kit S.; Birney, Damian P.
Abstract: Age related cognitive decline comes at a significant economic, social, and health cost. Interventions that prevent or slow cognitive decline and encourage positive ageing have potential to produce significant societal benefits and are a rapidly growing enterprise. Currently little is known about how individual difference factors influence adherence to the training regimes and training outcomes. The aim of the present study was to identify the personality and metacognitive beliefs that predict individuals' adherence to a regular training regime and the likelihood that they discontinue training. A sample of 831 older Australians drawn from registered users of a commercial brain training program, performed a range of personality and non-cognitive measures, specifically: need for cognition, implicit theories of intelligence, mastery beliefs, memory self-concept, and big-5 personality factors. The training frequency and performance of participants was tracked over an 18-month period. The results suggest that, within a sample of existing brain trainers, openness to experience, need for cognition, and age predicted training discontinuation. Furthermore, a regression analysis indicated that openness to experience, implicit theories of intelligence, and age influenced game performance. Implications of such findings for the effective design and application of cognitive training for encouraging positive ageing are discussed. Highlights: The personality and motivational factors that impact cognitive training performance and adherence were examined. Openness to experience, need for cognition, and age predicted cognitive training discontinuation. Openness to experience, implicit theories of intelligence, and age predicted game performance.